2020
DOI: 10.1063/1.5132614
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear correlations in multifractals: Visibility graphs of magnitude and sign series

Abstract: Correlations in multifractal series have been investigated, extensively. Almost all approaches try to find scaling features of a given time series. However, the analysis of such scaling properties has some difficulties such as finding a proper scaling region. On the other hand, such correlation detection methods may be affected by the probability distribution function of the series. In this article, we apply the horizontal visibility graph algorithm to map stochastic time series into networks. By investigating… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 62 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Mixed multifractal analysis has been emerged in such a field to model the nonlinear correlation in time series and/or their volatility to understand better the dependence between markets' indices. See [12,14,38,44].…”
Section: On the Utility Of Mixed Multifractal Analysis And Motivationsmentioning
confidence: 99%
“…Mixed multifractal analysis has been emerged in such a field to model the nonlinear correlation in time series and/or their volatility to understand better the dependence between markets' indices. See [12,14,38,44].…”
Section: On the Utility Of Mixed Multifractal Analysis And Motivationsmentioning
confidence: 99%
“…This type of correlation is generally driven by larger-scale processes such as climate change, natural cycles, and anthropogenic emissions [ 10 , 18 20 ]. Nonlinear correlation (NC) reflects the nonlinearity and complexity of stochastic climate time series [ 21 ]. Time series of air temperature anomalies reflect the complex dynamics of climate system on different scales; thus, it is actually a mixture of white noise (uncorrelated), STC, LTC and NC [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the nonlinearity of the original time series can be assessed by applying DFA or MFDFA to the decomposed series of magnitude and sign derived from the original time series [ 24 , 33 35 ]. However, some studies have indicated that the presence of correlation in the magnitude series alone is not a definitive indicator of nonlinearity in the original time series [ 21 ]. Additionally, the successful application of DFA and MFDFA is influenced by factors such as the polynomial order, the scaling region, and the probability distribution function (PDF) of the series [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations